UNE ÉCOLE PACIFIQUE DANS UN MILIEU SENSIBLE. QUE PEUT-ON FAIRE? (Universidad de Murcia, 2002)
This article, which has a more complete summary in Spanish, sustains that there are many different causes of violence in schools and that schools need to take measures that are adapted to their context and that allow the prevention of and attention to these problems. The measures taken in France from 1975 onwards are analyzed form a historical view point. 1975 was the year when the first episodes of violence in schools appeared in France and the date of the first questionnaires and reports about the phenomenon and the first measures taken to protect schools from exterior dangers. The article focuses specifically on the wide range of measures taken in the last decade, intended to improve the atmosphere in schools, «opening» them to the outside world; these measures have teen particularly directed at areas whose sociological characteristics require special attention. The last part of the article is an analysis of the structural violence that exist in French schools. The end of the article defends the idea that success in the prevention and treatment of violence in schools is related to the training of strong teaching teams and dialogue between all the members of the school community and its environment which allows the discussion of real problems and the arrival at adequate solutions.